Religion and Family Resilience in Urban Communities - Truna, Dody S.; Hanifah, Hani; Guntara, Yudi; Muhsin, Fuad; Atamimi, Abdul Basit (International Journal of Psychosocial Rehabilitation, 2020)
This research is aimed to elaborate the construction of religious thinking movement through building sakinah family and fostering Aisyiyah organization programs that provide services in improving family resilience in Garut district. This study applied a qualitative method with a phenomenological approach. The research findings showed facts and actual social phenomena regarding family resilience in urban communities. A strong family is that can survive and instill social values  from an early age in terms of religious norms and regulations that build a sakinah family. Religion funtions to hold strong control and absolute instructions for humans. Therefore, the main role and function of family in Garut district are to achieve progress and success of the nation.